Urine Exosomal AMACR Is a Novel Biomarker for Prostate Cancer Detection at Initial Biopsy - Jin, Xin; Ji, Jin; Niu, Decao; Yang, Yuchen; Tao, Shuchun; Wan, Lilin; Xu, Bin; Chen, Shuqiu; Wang, Fubo; Chen, Ming (Frontiers in Oncology, 2022)
Objectives: To identify and multi-center validate urine exosomal AMACR (UE-A) as a novel biomarker to improve the detection of prostate cancer (PCa) and clinically significant PCa (Gleason score ≥ 7) at initial prostate biopsy. Methods: A total of 289 first-catch urine samples after the digital rectal exam (DRE) were collected from patients who underwent prostatic biopsy and excluded 17 patients due to incomplete clinical information. Urine exosomes were purified, urinary exosomal AMACR (UE-A) was measured by enzyme-linked immunosorbent assay (ELISA). The diagnostic performance of UE-A was evaluated by receiver operating characteristic (ROC) analysis, decision curve analysis (DCA) and waterfall plots. Results: The expression of AMACR in PCa and csPCa was significantly higher than that in BPH and non-aggressive (P<0.001). The UE-A presented good performance in distinguishing PCa from BPH or BPH plus non-significant PCa (nsPCa) from csPCa with the area under ROC curve (AUC) of 0.832, 0.78, respectively. The performance of UE-A was further validated in a multi-center cohort of patients with an AUC of 0.800 for detecting PCa and 0.749 for detecting csPCa. The clinical utility assessed by DCA showed that the benefit of patients using UE-A was superior to PSA, f/t PSA and PSAD in both training cohort and validation cohort in terms of all threshold probabilities. Setting 95% sensitivity as the cutoff value, UE-A could avoid 27.57% of unnecessary biopsies, with only 4 (1.47%) csPCa patients were missed. Conclusions: We demonstrated great performance of UE-A for the early diagnosis of PCa and csPCa. UE-A could be a novel non-invasive diagnostic biomarker to improve the detection of PCa and csPCa.